Pediatric mortality in the multipurpose intensive care unit of Sylvanus Olympio Teaching Hospital (CHU SO) of Lomé (Togo). - P. Egbohou; T. Mouzou; H. D. Sama; A. Sarakawabalo; L. Randolph; K. Tomta (Pediatric Anesthesia and Critical Care Journal (PACCJ), 2019)
Introduction The objective of the study is to analyze pediatric deaths (0 to 15 years) registered in the Intensive Care Unit (ICU) of the Sylvanus Olympio Teaching Hospital (CHU SO) in Lome. Material and methods It was a retrospective study, during the period from No- vember 2012 to October 2015 (3 years). We included all exploitable records of deceased patients aged 0 to 15 years. Results 70 deaths were recorded out of 260 files included; rate: 26.9%. The mean age of patients who died was 44.9±56 months; age groups: below 1month: 17(24.3%), 1 to 24 months: 21 (30%), 25 to 60 months: 10 (14.3%), and 60 to 180 months: 22 (31.4%). Male represented 55, 7% (39deaths), ratio: 1, 26. High lethality was observed in children below 1 month (43.5%, p = 0.07) and in females (33.3%, p = 0.04). Surgical pathologies represented 90% (63 deaths out of 70) and medical pathologies 10% (7 deaths). Medical pathologies were more lethal (46.7%) than surgical pathologies (25.7%), p = 0.04. Digestive surgery: 34 (48.6%) followed by trauma 14 (20%) of which 13 were severe traumatic brain injury, and severe burns 13 (18.6%) were the most represented surgical eti- ologies. Conclusions the etiologies of pediatric deaths in the ICU of the CHU SO of Lome are dominated by surgical pathologies, par- ticularly digestive, traumatic and severe burns.